PENGEMBANGAN MODEL HIPOTETIK PERMAINAN BOLA BASKET UNTUK TUNANETRA - Ardisal, Ardisal; Triswandari, Retno; Safaruddin, Safaruddin; Ardiyus, Muhammad Fauzan (STKIP Pesisir Selatan, 2025)
Adaptive physical education is a direct service that can be provided to children with special needs, to meet the individual physical-motor needs of students with disabilities. A case study shows that blind people are less motivated to play sports, one of which is playing basketball. So, development research was carried out by creating a basketball game model for the blind. This game model was designed by modifying the facilities and rules in the game of basketball and adapted to the characteristics of the visually impaired. Researchers used a research and development design with several modified stages. Validation was carried out using the Focus Group Discussion technique, namely discussions with users, namely the visually impaired, and the model was validated by experts using a validation test instrument with a Likert scale reference. This instrument contains three aspects of assessment, namely suitability, usefulness and appropriateness of playing basketball for the blind. The results of the analysis of the blind basketball game model showed that the percentage of suitability aspects = 81%, usability aspect = 100%, feasibility aspect = 77%. So the blind basketball game model is suitable, useful, and worthy of being developed and tested.